Redescriptions, new synonymy, new combination and new records of Bacis Dejean, 1836 and Oligocorynus Dejean, 1876 (Coleoptera: Erotylidae: Erotylinae) for Colombia - Lopes, Peterson Lásaro; Gasca-Álvarez, Héctor Jaime; Skelley, Paul E. (Zootaxa, 2020)
Bacis nigropictus Crotch, 1876 and Phricobacis flavomaculatus Mader, 1943 are redescribed. Redescriptions are provided with illustrations of diagnostic characters. Based upon the study of type material, Zonarius limbatus Kuhnt, 1910 is considered a new synonym of B. nigropictus. A lectotype is designated for Zonarius limbatus Kuhnt, 1910. Based on character analyses, Phricobacis flavomaculatus is here transferred to the genus Oligocorynus Dejean, 1836, becoming Oligocorynus flavomaculatus (Mader), new combination. Bacis nigropictus is newly listed for Colombia and O. flavomaculatus is considered new country record from Colombia.